The Lies We Conjure - Henning, Sarah (New York : Tor Teen/Tor Publishing Group, 2024)
Knives Out meets The Inheritance Games with magic in this standalone supernatural thriller by Sarah Henning: thirteen witches, a locked-room murder, and two non-magical sisters trapped in a deadly whodunit.Ruby and her sister, Wren, are normal, middle-class Colorado high school students working a summer job at the local Renaissance Fest to supplement their meager college savings.So when an eccentric old lady asks them to impersonate her long-absent grandchildren at a fancy dinner party at the jaw-dropping rate of two grand$1 (Beach$1 (Bfor a single night$1! = (BWren insists it$1 (Bs a no-brainer. Make some cash, have some fun, do a good deed.But less than an hour into the evening at the mysterious Hegemony Manor, Ruby is sure she must have lost her mind to have agreed to this.The hostess is dead, the gates are locked, and a magical curse ensures no one can leave until they solve both her murder and the riddles she left behind$1 (Bin just three days. Because everyone else at this party is a powerful witch. And if the witches realize Ruby and Wren are imposters? The sisters won$1 (Bt make it out of Hegemony Manor alive.s
new ya book fall 2024.
Keywords: Sisters -- Fiction; Supernatural -- Fiction; Witches -- Fiction; Murder -- Fiction; Impersonation -- Fiction; Thriller fiction; Fantasy fiction; Young adult fiction